Beyond Entertainment: Relevansi BTS Sebagai Icon Korean Wave dan Nation Branding Korea Selatan - Riza Emilly Hanifa; Riva Davia; Evy Angela Siringo Ringo (Social Issues Quarterly, 2023)
This research paper examines the cultural phenomenon of BTS, a globally recognized South Korean boy band, and its impact on the Korean Wave and South Korea’s nation branding efforts. Through qualitative methods and a descriptive approach, this study aims to explore the multifaceted dimensions of BTS’s success and its implications for South Korea’s global image. The study adopts a qualitative research method, content analysis of media sources and literature review. A diverse range of participants, including BTS fans, industry experts, and South Korean government officials, were selected to provide comprehensive insights into the subject matter. The analysis is focused on understanding the factors contributing to BTS’s popularity, the ways in which the group has influenced perceptions of South Korea, and the strategic efforts employed by the South Korean government to leverage BTS’s success in their nation branding endeavors. Findings reveal that BTS’s success can be attributed to a combination of musical talent, engaging performances, relatable content, and an active online presence. Moreover, the study highlights the significant impact of BTS in enhancing South Korea’s soft power and promoting the Korean Wave globally. BTS has contributed to reshaping perceptions of South Korea and generating interest among international audiences.